Analysis of Public Service Quality at the Investment and One-Stop Integrated Service Office of Sukabumi City - Husna, Asmaul; Sunarya, Erry; Suwiryo, Darmo H. (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the quality of public services provided by the Investment and One-Stop Integrated Services Office (DPMPTSP) of Sukabumi City, particularly in issuing Trade Business Licenses (SIUP). Employing a qualitative descriptive approach, data were gathered through in-depth interviews, non-participant observation, and documentation. The research applied the SERVQUAL model, assessing five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Results show that DPMPTSP services are generally perceived as “good,” with tangible elements (infrastructure and appearance of staff) considered adequate. Reliability is reflected in adherence to SOPs, though some issues arise from network disruptions and application completeness. Responsiveness and empathy are rated positively by service users, while assurance is supported by staff professionalism and transparency. The use of the Online Single Submission (OSS) system contributes to the efficiency and legality of business licensing. However, challenges remain in digital literacy among applicants and occasional delays. The study concludes that continuous improvement in service speed, transparency, and system optimization is essential. DPMPTSP is recommended to enhance digital infrastructure, provide regular training, and expand public information access to strengthen trust and satisfaction in public service delivery.